2007
DOI: 10.1186/1465-9921-8-71
|View full text |Cite
|
Sign up to set email alerts
|

LPS induces IL-10 production by human alveolar macrophages via MAPKinases- and Sp1-dependent mechanisms

Abstract: Background: IL-10 is a cytokine mainly produced by macrophages that plays key roles in tolerance to inhaled antigens and in lung homeostasis. Its regulation in alveolar macrophages (HAM), the resident lung phagocytes, remains however unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
96
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 53 publications
15
96
1
1
Order By: Relevance
“…40 LPSinduced activation of Sp1 in turn regulates the transcription of the human IL-10 gene. 35,38,39,41 In conclusion, this study demonstrated that the transcription factors PU.1, Spi-B and Sp1 in B cells bound to the À1087 site in the IL-10 promoter region. Using transfection of the DG75 B-cell line, we showed differences in promoter activity for the ACC and GCC haplotypes.…”
Section: Sp1 Transcription Factor Binds To the Il-10 à1087 G-allele Lsupporting
confidence: 52%
See 1 more Smart Citation
“…40 LPSinduced activation of Sp1 in turn regulates the transcription of the human IL-10 gene. 35,38,39,41 In conclusion, this study demonstrated that the transcription factors PU.1, Spi-B and Sp1 in B cells bound to the À1087 site in the IL-10 promoter region. Using transfection of the DG75 B-cell line, we showed differences in promoter activity for the ACC and GCC haplotypes.…”
Section: Sp1 Transcription Factor Binds To the Il-10 à1087 G-allele Lsupporting
confidence: 52%
“…35,38,39 The mechanism of LPS stimulation involves the binding to proteins, presentation to the cell surface receptor CD14 and subsequently the toll-like receptor 4 (TLR4). 40 LPSinduced activation of Sp1 in turn regulates the transcription of the human IL-10 gene.…”
Section: Sp1 Transcription Factor Binds To the Il-10 à1087 G-allele Lmentioning
confidence: 99%
“…Collectively, these data suggest that C5a-dependent ERK1/2 phosphorylation selectively suppresses LPS-induced IL-6 and TNF production in macrophages. Interestingly, although the literature suggests that ERK1/2 is involved in TLR-induced IL-10 production from human macrophages (15,34), we found in the present study that C5a enhanced LPS-mediated IL-10 production in an ERK1/2-independent, but G ai -dependent, manner (Fig. 3C).…”
Section: Temporal Study Of C5ar/tlr4 Crosstalk In Hmdmscontrasting
confidence: 28%
“…LPS-induced activation of Sp1 expression is involved in the regulation of the transcription of the human IL-10 gene [34][35][36][37] and one Sp1-binding site was identified in the region immediately upstream of À571 in the IL-10 promoter. 38 LPS activates the three mitogen-activated protein kinase (MAPK9) pathways ERK, JNK and p38 and, thereby, transcription factors that are involved in gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…38 LPS activates the three mitogen-activated protein kinase (MAPK9) pathways ERK, JNK and p38 and, thereby, transcription factors that are involved in gene regulation. 35 Chanteux et al 35 showed that ERK, p38, JNK as well as Sp1 are essential in LPS-induced IL-10 expression in human alveolar macrophages. In a study by Perkins et al 39 on HIV transcription activation, it was shown that Sp1 specifically interacted with the amino-terminal of p65.…”
Section: Discussionmentioning
confidence: 99%